Effective Communication in Growing Tasamuh Values for the Alpha Generation - Boy, Boini; Zaenuddin Hudi Prasojo, Zaenuddin Hudi Prasojo; Wahab, Wahab (JASNA : Journal For Aswaja Studies, 2024)
Effective communication is an exchange of ideas, feelings and information that can produce changes in behavior, so that a good relationship is established between the sender and recipient of the message. Tasamuh is an attitude of tolerance that must be created within the scope of Islamic education in this century. The current problem is that we see various learning in schools that are unable to achieve learning goals simply because of dis-communication between teachers and students and a lack of mutual respect between each other. The problem that often occurs and is the simplest in communication is that listening skills tend to be lacking. This research is qualitative in nature, using book contents as a source of information to analyze and understand various theories or concepts through book research. This research was carried out using a descriptive approach with qualitative methods as part of collecting the required data. The objectives of this research are: 1. What is the participation of the Alpha generation in carrying out effective learning? 2. What is the teacher's view of the impact of effective learning? 3. What is the teacher's view before and after carrying out effective learning? The theoretical implications of the results of this research increasingly emphasize that religious tolerance and morality are a unified whole in Islamic education which refers to acceptance of differences in gender, race and lifestyle.